THE EFFECTS OF SHORT TERM AND LONG TERM NAAD YOGA MEDITATION TRAINING ON MINDFULNESS IN UNIVERSITY STUDENTS - Joshi, Navdeep; Sahrawat, Mamta; Singh, Vikram (International Journal of Research -GRANTHAALAYAH, 2021)
Introduction: Meditation has been practiced since times immemorial consciously or unconsciously by the people from different origins and the trend has caught more attention of the researchers worldwide due to popularity of yoga in the recent years. Method: Internet-delivered online NAAD yoga meditation training for 6 weeks was being imparted to the university level participants (n = 67) and were assessed before, during and after treatment, and their compliance with the intervention they received was tracked online. In the randomized controlled trail (RCT) study, the treatments were received at a time, place, and computer of the participants’ choosing with the proviso that the training be completed live and online during each of 6 successive weeks (6 days a week with a 32 minutes session each day). The trait MAAS, a 15-item scale designed to assess individual differences in the frequency of mindful states over time questionnaire was being used as tool to assess (also known as trait) mindfulness amongst all the participants. Results: Both a short term (3 weeks) long-term (6 weeks) NAAD yoga meditation programs elicited a statistically significant improvement on MAAS scores (p<.000).